2021
DOI: 10.31234/osf.io/6ebuq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reward sensitivity and internalizing symptoms during the transition to puberty: An examination of 9-and 10-year-olds in the ABCD Study

Abstract: Early pubertal timing has been linked to increased risk for internalizing disorders. Work in older adolescents and adults suggests that heightened reward sensitivity may buffer risk for internalizing symptoms, but few studies have investigated these associations during the early transition to puberty, a window of vulnerability to mental health risk. In this preregistered study, we investigated the associations among pubertal timing, internalizing symptoms, and reward sensitivity in 11,243 9-10 year-olds from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…In particular, whether the most accurate and reliable judgments of it come from children themselves or from their parents. While the majority of the ABCD literature uses the parent reported PDS ( Demidenko et al, 2021 ; McNeilly et al, 2021 ; Thijssen et al, 2020 ), there are also instances of the youth reported PDS ( Argabright et al, 2022 ) and an average of the parent and youth reported PDS being used ( Petrican et al, 2021 ). This multiverse study provided a unique opportunity to compare the consequences of researchers utilizing each of these three operationalizations of puberty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, whether the most accurate and reliable judgments of it come from children themselves or from their parents. While the majority of the ABCD literature uses the parent reported PDS ( Demidenko et al, 2021 ; McNeilly et al, 2021 ; Thijssen et al, 2020 ), there are also instances of the youth reported PDS ( Argabright et al, 2022 ) and an average of the parent and youth reported PDS being used ( Petrican et al, 2021 ). This multiverse study provided a unique opportunity to compare the consequences of researchers utilizing each of these three operationalizations of puberty.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies focused on neurodevelopment have used latent factors of the family environment ( Thijssen et al, 2020 , 2022 ), bio-psycho-social ecologies ( Gonzalez et al, 2020 ), neighborhood and family income/stress ( Demidenko et al, 2021 ; Ip et al, 2022 ; Sripada et al, 2021 ; Taylor et al, 2020 ) and material deprivation/threat/social support ( DeJoseph et al, 2022 ; Petrican et al, 2021 ), or individual scales of family-to-needs ratios ( Gonzalez et al, 2020 ; Rakesh et al, 2021), poverty levels ( Ellwood-Lowe et al, 2021 ), parental education ( Rakesh et al, 2021a , b ), area deprivation indices (Rakesh et al, 2021; Rakesh et al, 2021) and parental acceptance (Rakesh et al, 2021). As for measures of pubertal development (see reviews regarding measures and correspondence of pubertal scales: Cheng et al (2021) and Herting et al (2021) ), published works using ABCD data have used parent-reported pubertal development ( Demidenko et al, 2021 ; McNeilly et al, 2021 ; Thijssen et al, 2020 , 2022 ) or youth/parent reported averages of pubertal development ( Petrican et al, 2021 ). Given variations in the analytic choices regarding measures of the family environment and puberty, the overall goal of the current analysis is to use a multiverse approach to understand the nuanced associations among stressful family environmental experiences, puberty and neurodevelopment when using broad measures (i.e., latent factors) that are comprised of multiple scales as well as specific measures (i.e., individual scales) that are based on individual scales.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, whether the most accurate and reliable judgments of it come from children themselves or from their parents. While the majority of the ABCD literature uses the parent reported PDS (Demidenko et al, 2021;McNeilly et al, 2021;Thijssen et al, 2020), there are also instances of the youth reported PDS (Argabright et al, 2022) and an average of the parent and youth reported PDS being used (Petrican et al, 2021). This multiverse study provided a unique opportunity to compare the consequences of researchers utilizing each of these three operationalisations of puberty.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies focused on neurodevelopment have used latent factors of family environment (Thijssen et al, 2020), biopsycho-social ecologies (Gonzalez et al, 2020), neighborhood and family income/stress (Demidenko et al, 2021;Ip et al, 2022;Sripada et al, 2021;Taylor et al, 2020) and material deprivation/threat/social support (DeJoseph et al, 2022;Petrican et al, 2021), or individual scales of family-to-needs ratios ( sss Gonzalez et al, 2020;, poverty levels (Ellwood-Lowe et al, 2021), parental education , area deprivation indices (Rakesh, Seguin, et al, 2021; and parental acceptance (Rakesh, Seguin, et al, 2021). As for measures of pubertal development (see reviews regarding measures and correspondence of pubertal scales: Cheng et al (2021) and Herting et al (2021), published works using ABCD data have used parent-reported pubertal development (Demidenko et al, 2021;McNeilly et al, 2021;Thijssen et al, 2020) and youth/parent reported averages of pubertal development (Petrican et al, 2021). Given variations in the analytic choices regarding measures of the family environment and puberty, the overall goal of the current analysis is to use a multiverse approach to understand the nuanced associations among stressful family environmental experiences, puberty and neurodevelopment when using broad measures (i.e., latent factors) that are comprised of multiple scales as well as specific measures (i.e., individual scales) that are based on individual scales.…”
Section: Measurements Of Family Environmental Puberty and Brainmentioning
confidence: 99%